Cross-Country Experience in Reducing Net Foreign Liabilities : Lessons for New Zealand - Ding, Ding (IMF Working Papers; Working Paper ;, 2014)
This paper studies the dynamics of net foreign liabilities across a number of countries. Our historical analysis suggests that an orderly reduction in a country's net foreign liabilities has mostly occurred when there was significant improvement in gross public savings through deliberate fiscal consolidation measures. Simulations of a dynamic general equilibrium model calibrated for New Zealand indicates that sustained government deficit reduction could improve the country's net foreign assets by about half of the accumulated public savings. However, given New Zealand's relatively strong fiscal positions and previous work noting structurally low household savings, an orderly improvement in New Zealand's external position in the medium term will depend on a structural improvement in private savings.